2017
DOI: 10.1021/acscatal.7b00737
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective cis-Vinylcyclopropanation via a Gold(I)-Catalyzed Retro-Buchner Reaction under Mild Conditions

Abstract: A highly stereoselective gold(I)-catalyzed cis-vinylcyclopropanation of alkenes has been developed. Allylic gold carbenes, generated via a retro-Buchner reaction of 7-alkenyl-1,3,5-cycloheptatrienes, react with alkenes to form vinylcyclopropanes. The gold(I)-catalyzed retro-Buchner reaction of these substrates proceeds by simple heating at a temperature much lower than that required for the reaction of 7-aryl-1,3,5-cycloheptatrienes (75 °C vs 120 °C). A newly developed Julia–Kocienski reagent enables the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 131 publications
1
50
0
Order By: Relevance
“…Although some 7‐styryl‐1,3,5‐cycloheptatrienes can be prepared using tropylium tetrafluoroborate as shown in Scheme , a more reliable and general method is based on the use of the Julia‐Kocienski olefination employing sulfone 39 (Scheme ) …”
Section: Cyclopropanation Via Retro‐buchner Reaction Of Cycloheptatrimentioning
confidence: 99%
See 2 more Smart Citations
“…Although some 7‐styryl‐1,3,5‐cycloheptatrienes can be prepared using tropylium tetrafluoroborate as shown in Scheme , a more reliable and general method is based on the use of the Julia‐Kocienski olefination employing sulfone 39 (Scheme ) …”
Section: Cyclopropanation Via Retro‐buchner Reaction Of Cycloheptatrimentioning
confidence: 99%
“…Sulfone 39 can be prepared in multi‐gram scale and stored indefinitely. Treatment of this reagent with LiHMDS followed by the addition of commercially available aldehydes or ketones allows the synthesis of a wide range of 7‐vinyl and 7‐styryl‐1,3,5‐cycloheptatrienes, which can be also employed to generate gold(I) carbenes by retro‐Buchner reaction (Table ) …”
Section: Cyclopropanation Via Retro‐buchner Reaction Of Cycloheptatrimentioning
confidence: 99%
See 1 more Smart Citation
“…[15] (AE)-Laurokamurene B( 10)w as readily synthesized in good yield by simple hydrogenation of cyclopentadiene 7h in the presence of the Wilkinson catalyst (Scheme 3). Considering that (E)-7-(4-methylstyryl)cyclohepta-1,3,5-triene (2b), the cycloheptatriene required for the preparation of 7h,c an be readily obtained by the treatement of potassium (E)-(4-methylstyryl)trifluoroborate with tropylium tetrafluoroborate in almost quantitative yield, [3] this total synthesis requires just three steps and provides (AE)-10 in 39 %overall yield from commercially available starting materials,w hich compares favorably with previous syntheses of (AE)-10. [17] Cycloaurenones A-C (8a-c)feature a cis-decalin moiety, whereas the dysiherbols (9a-c)s how trans fusion of the A/B rings ( Figure 1).…”
Section: Entrymentioning
confidence: 99%
“…Wep reviously found that cationic gold(I) complexes promote the retro-Buchner reaction of 7-substituted 1,3,5-cycloheptatrienes,s uch as 1 and 2,v ia their norcaradiene tautomers,leading to reactive metal carbenes [1] [LAu = CHR] + 3 and 4 (Scheme 1), which react with alkenes to give cyclopropanes [2,3] or undergo intramolecular Friedel-Craftstype reactions. [4] Cyclopentenes were obtained by the formal (4+ +1) cycloaddition of gold(I) carbenes 3 with cyclobutenes or methylenecyclopropanes.…”
mentioning
confidence: 99%